Pengaruh Kompensasi terhadap Niat Keluar pada Tenaga Kerja Multigenerasi: Bukti dari Generasi X, Y, dan Z - Widyastuti Widarmasanti Wijono; Ramli Parulian Sitorus; Angka Utama; Fairuz Arta Abhipraya (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study investigates the impact of compensation on turnover intention among employees of PT ASN, with a specific focus on Generations X, Y, and Z. A sample of 100 respondents was drawn from a population of 315 employees using non-probability sampling through a purposive sampling technique. The research adopted a quantitative framework with survey data collection, utilizing an ordinal Likert scale. The data was analyzed using the SmartPLS 4 application using structural equation modeling-partial least squares (SEM-PLS). The findings reveal an adverse effect of Compensation towards Turnover Intention, suggesting that higher suitable compensation leads to a reduced Turnover Intention. Based on these results and available resources, HR at PT ASN may consider implementing a compensation strategy tailored to the preferences of each generation. For Generation X, which values long-term benefits such as pensions, insurance, and stability, the company could prioritize these forms of compensation. Generation Y may place more excellent value on recognition for contributions and opportunities for career development through training and growth. Finally, for Generation Z, PT ASN could offer more flexibility in its compensation structure, including project-based incentives and provisions for technology usage. Notably, Generation Z exhibits the lowest satisfaction with the current compensation policy, highlighting a need for more adaptable compensation options such as project-based incentives and greater access to technology. Addressing these issues may reduce turnover intention among Generation Z employees. A diversified compensation approach could strategically reduce turnover rates across these three generations. Compared to existing literature, this study provides a novel contribution to understanding the impact of compensation on turnover intention for X, Y, and Z generations. However, the quantitative approach does not fully capture other factors influencing turnover intention, such as psychological factors, job satisfaction, or organizational culture. In order to investigate these extra aspects in greater detail, future research should use a mixed-methods strategy that integrates both quantitative and qualitative techniques.